‘Just look at those shabby trains in Lisbon’: Post-arrival disappointment amongst Chinese migrants in Portugal - Cojocaru, O.; Gaspar, S.; Wang, X. (Journal of Ethnic and Migration Studies, 2025)
This article examines the disappointment experienced by affluent Chinese migrants in Portugal, revealing the discrepancy between their premigration expectations and post-arrival realities and how they overcome this mismatch through recalibration practices. Despite their financial advantage, Chinese migrants often express disappointment and discontent with their migration project, mostly stemming from frustrations with public service inefficiencies, insufficient infrastructure, and a lack of cultural stimulation compared to their experiences in China or other global cities. Drawing on 27 in-depth interviews with Golden Visa, D7 passive income visa, work and student mobility migrants, this paper shows how discontent often manifests as boredom in their daily lives in Portugal, as well as a byproduct of privilege and mediated expectations. However, this study indicates that feelings of disappointment upon arrival are not necessarily negative or incapacitating but instead can prompt a proactive reassessment of aspirations and result in adjustment practices such as revision of expectations and priorities, financial recalibration or onward migration.